Effect of apolipoprotein E genotype variation on the risk of premature ischaemic heart disease - Rashid, Faridah Abdul; Mustapha, Mohd Rafi
Apolipoprotein E is expressed by 3 allelic genes, £2, £3 and £4, on Chromosome 19. ApoE isoforms are distinguished by residues at positions 112 and 158. We analysed blood from 83 first year medical students for: Total cholesterol and triglycerides, HDLC, LDLC, ApoA-1 and B levels. For ApoE genotypes, DNA were extracted from huffy coat amplified by PCR, restricted by endonuclease, electrophoresed on polyacrylamide gel and visualised by ethidium bromide staining. The genotypes obtained were: E-3/3(64%), E-4/3(27%), E-3/2(5%), and E-4/2(4%), and gene frequencies were: £2(0.04), e3(0.80), £4(0.16). The E-3/3 genotype contributed to hypercholesterolemia, low HDLC, high LDLC high ApoB. The E-4/2 genotype gave the opposite effect of E-3/3. The E-4/3 genotype exhibited hypertriglyceridemia, low LDLC and low ApoB. The E-3/2 genotype manifested normotriglyceridemia, high HDLC, low ApoA-I and low AlB ratio. We conclude that the E-3/3 genotype had the highest risk for premature heart disease. Those with the other genotypes (E-4/3, E-4/2 and E-3/2) had lower risk of premature heart disease.